Concrete containing heterogeneous mineral admixture and preparation method thereof
By using formulas containing heterogeneous mineral blends in concrete, including modified island fibers and montmorillonite, the problem of increasing concrete voids caused by construction waste is solved, and the mechanical properties and durability of concrete are significantly improved.
Patent Information
- Application Number
- CN202411972318.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-25
AI Technical Summary
The use of construction waste composed of broken bricks and bricks and tile fragments may lead to an increase in voids in concrete, affecting the mechanical properties of concrete.
Concrete formulas containing heterogeneous mineral blends are used, including sand, gravel, silicate cement, fly ash, construction waste, modified island fibers, montmorillonite and water reducers. Through the addition of modified island fibers and montmorillonite, the crack resistance and compactness of the concrete are improved.
It significantly improves the mechanical properties, crack resistance, durability and structural strength of concrete, reduces the micro-cracks of concrete, and extends the service life of concrete.
Smart Images

Figure BDA0005219734590000101 
Figure BDA0005219734590000111
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of concrete, and in particular to concrete containing heterogeneous mineral admixtures and a preparation method thereof. Background Art
[0002] Concrete is an artificial stone material made of cementitious materials (such as cement), granular aggregates (such as sand and stone, also known as aggregates), water and admixtures in a certain proportion. Among them, cement, as the main cementitious material, plays the role of bonding other materials; sand and stone, as aggregates, provide the structural strength of concrete; water and cement undergo hydration reaction after mixing, which hardens the concrete and forms a hard structure; admixtures include other inorganic mineral powders such as fly ash and slag powder to further improve the performance of concrete.
[0003] Construction waste refers to various solid wastes generated during construction activities, including broken stones, brick and tile fragments and other wastes. Construction waste can be used in concrete after certain treatment, which not only realizes the recycling of resources but also reduces the production cost of concrete. However, the use of construction waste composed of broken bricks and brick and tile fragments may cause more voids in concrete, thereby affecting the mechanical properties of concrete. Summary of the invention
[0004] In order to improve the problem that construction waste may affect the mechanical properties of concrete, the present application provides a concrete containing heterogeneous mineral admixtures and a preparation method thereof.
[0005] The present application provides a concrete containing heterogeneous mineral admixtures, which adopts the following technical solution: A concrete containing heterogeneous mineral admixtures comprises the following raw materials, measured by weight: 80-90 parts of sand, 120-130 parts of gravel, 50-60 parts of Portland cement, 30-40 parts of fly ash, 40-50 parts of construction waste, 80-100 parts of deionized water, 35-45 parts of modified sea island fibers, 25-30 parts of montmorillonite, and 3-5 parts of water reducing agent.
[0006] By adopting the above technical scheme, sand is used as fine aggregate in concrete, and gravel is used as coarse aggregate in concrete. Together with the coarse aggregate, they constitute the skeleton of concrete and support the structure of concrete. Sand can fill the gaps between silicate cement and gravel, making the concrete structure more compact and improving the strength and durability of concrete. Gravel can fill the larger gaps in concrete and form a dense structure together with sand and silicate cement, thereby improving the density and durability of concrete.
[0007] Portland cement reacts with water to produce hydration products such as hydrated calcium silicate, calcium hydroxide and hydrated calcium aluminate. These products gradually harden and bond aggregates such as sand and gravel together to form the structure of concrete. Fly ash can fill the pores in concrete, form a dense structure, and improve the durability and strength of concrete. Construction waste, as one of the raw materials of concrete, realizes the recycling of resources. The mixture of construction waste, sand, gravel and fly ash improves the strength, durability and impermeability of concrete. Water reducer can significantly improve the workability of concrete, including fluidity, cohesion and water retention, making concrete easier to handle during pouring and molding, and reducing the risk of stratification and segregation.
[0008] Modified island fibers are added to concrete to improve the wear resistance, toughness, and mechanical properties of concrete, effectively inhibit shrinkage cracks in the hardening process, and improve the crack resistance of concrete. Modified island fibers form a three-dimensional network in concrete, which can absorb and disperse stress and prevent the expansion of cracks. When the concrete is subsequently impacted, it can better absorb and disperse energy, reduce structural damage, and extend the service life of concrete. Montmorillonite can participate in the hydration process of cement, generate a large amount of CSH gel, fill the micropores and microcracks in the concrete, increase the bonding force of each component, significantly improve the microstructure of concrete, improve its density, and subsequently improve the mechanical properties of concrete. The concrete obtained by mixing various raw material components has good mechanical properties, crack resistance, durability, and structural strength.
[0009] Preferably, the method for preparing the construction waste comprises the following steps: (1) crushing the construction waste into pieces with a particle size of 1-3 mm, dispersing them in anhydrous ethanol, soaking them for 1-2 hours, drying them, and then dispersing them in deionized water, adding a silane coupling agent, stirring them for 1-2 hours, filtering them, and drying them to obtain pretreated construction waste; (2) crushing the bamboo, sieving, and then dispersing in a sodium hydroxide solution, stirring for 1-2 hours, washing with water, and drying to obtain pretreated bamboo powder; (3) Dispersing the pretreated construction waste in step (1) in deionized water, adding the pretreated bamboo powder and modified peach gum powder in step (2), stirring at a temperature of 70-75° C. for 1-2 hours, and drying to obtain construction waste.
[0010] By adopting the above technical scheme, the construction waste is crushed, cleaned with anhydrous ethanol to remove residual substances such as oil and grease on the surface of the construction waste, and then dispersed in deionized water, and a silane coupling agent is added. The silane coupling agent forms a layer of chemical bonding on the surface of the construction waste, thereby improving the interface bonding strength between the construction waste and other materials and enhancing the bonding force between the materials.
[0011] Bamboo is crushed to form bamboo powder, and sodium hydroxide is used to pre-treat the surface of the bamboo powder to remove organic matter in the bamboo powder, increase the surface roughness of the bamboo powder, make the surface have more active groups, and improve the adsorption of the bamboo powder.
[0012] Pretreated bamboo powder, pretreated construction waste and modified peach gum powder are mixed. Bamboo powder has good adsorption capacity and can be loaded on the surface and pores of construction waste, thereby improving the mechanical properties, wear resistance and crack resistance of construction waste. Modified peach gum powder has good viscosity, which makes bamboo powder adhere to the surface of construction waste and fill the pores of bamboo powder and construction waste, thereby improving the toughness and durability of construction waste, thereby subsequently improving the crack resistance and compression resistance of concrete.
[0013] Preferably, the mass ratio of the construction waste, bamboo and modified peach gum powder is 1:0.5-0.7:0.08-0.09.
[0014] By adopting the above technical scheme, the mass ratio of construction waste, bamboo and modified peach gum powder is further limited within a certain range, the mechanical properties and durability of construction waste are improved, bamboo powder can be loaded on the surface and pores of construction waste, and the toughness and durability of construction waste are improved. Modified peach gum powder has good viscosity, so that bamboo powder adheres to the surface of construction waste and fills the pores between bamboo powder and construction waste. The cellulose in peach gum powder can form fine fiber bundles in construction waste, increase the internal bonding force of construction waste, and improve the strength and durability of construction waste. Construction waste, bamboo and modified peach gum powder have a synergistic effect, jointly improve the mechanical properties and mechanical structure of construction waste, and subsequently increase the crack resistance and compression resistance of concrete.
[0015] Preferably, the preparation method of the modified peach gum powder comprises the following steps: dispersing peach gum in deionized water at a temperature of 70-75° C., adding citric acid, sodium carboxymethyl cellulose and slag powder, stirring for 2-3 hours, drying, and grinding to obtain modified peach gum powder.
[0016] By adopting the above technical scheme, peach gum is dissolved in hot water, citric acid is added to promote the dissolution of peach gum in water to form a more uniform solution, sodium carboxymethyl cellulose and slag powder are added, and sodium carboxymethyl cellulose forms a high-viscosity solution in water, thereby improving the stability of the system, and mixing with peach gum to further increase the viscosity and stability of the system. Slag powder has good mechanical properties and can be embedded in the system structure formed by peach gum and sodium carboxymethyl cellulose to improve the mechanical properties of the system. It is subsequently applied to construction waste to improve the density, crack resistance, compressive strength and durability of the construction waste, thereby improving the corresponding performance of concrete.
[0017] Preferably, the mass ratio of the peach gum, sodium carboxymethyl cellulose and slag powder is 1:0.2-0.3:0.4-0.5.
[0018] By adopting the above technical scheme, the mass ratio of peach gum, sodium carboxymethyl cellulose and slag powder is further limited within a certain range, so as to improve the mechanical properties, viscosity and stability of peach gum. Peach gum can form a colloidal solution in water, and the viscosity of the solution is increased. Sodium carboxymethyl cellulose contains multiple carboxymethyl groups in its molecular structure. When peach gum and sodium carboxymethyl cellulose are mixed, the introduction of carboxymethyl groups in the molecular structure of sodium carboxymethyl cellulose improves the solubility and thickening of peach gum in water, and forms a stable solution.
[0019] Slag powder has good mechanical properties, impermeability, crack resistance and durability. It can be embedded in the system structure formed by peach gum and sodium carboxymethyl cellulose to improve the mechanical properties of the system. Peach gum, sodium carboxymethyl cellulose and slag powder have a synergistic effect and are subsequently applied to construction waste to improve the crack resistance, compressive strength and durability of construction waste, thereby improving the corresponding performance of concrete.
[0020] Preferably, the method for preparing the modified sea island fiber comprises the following steps: (1) Dispersing the sea island fibers in ammonia water, stirring for 1-2 hours, washing with water, and then dispersing in anhydrous ethanol, soaking, and drying to obtain pretreated sea island fibers; (2) dispersing graphene in ethylene glycol, adding nano-silicon dioxide, ultrasonicating for 1-2 hours, filtering and drying to obtain pretreated graphene; (3) Dispersing the pretreated sea island fibers of step (1) in deionized water, adding the pretreated graphene and modified chitosan of step (2), stirring at a temperature of 80-85° C. for 2-3 h, and drying to obtain modified sea island fibers.
[0021] By adopting the above technical solution, the surface of the sea island fiber is treated with ammonia water to increase the specific surface area of the sea island fiber, so that the surface of the sea island fiber has a porous structure, the adsorption of the sea island fiber is improved, and it is helpful to load with other components later.
[0022] Graphene has good mechanical strength and thermal stability. When dispersed in ethylene glycol, nano-silica can be loaded on the surface of graphene to further improve the mechanical properties of graphene. Graphene is easy to agglomerate, and the addition of nano-silica improves the dispersion of graphene and prevents it from re-aggregating, thereby improving the stability of the system.
[0023] Pretreated graphene, pretreated island fibers and modified chitosan are mixed. The pretreated graphene can be loaded on the surface of the pretreated island fibers. The modified chitosan has a certain viscosity, so that the graphene can stably adhere to the surface of the island fibers. The high strength and high modulus of graphene can significantly enhance the mechanical properties of the island fibers, such as tensile strength, bending strength and impact strength. The modified chitosan further improves the performance stability of the modified island fibers, which can be subsequently used in concrete to improve the strength, toughness, durability and stability of the concrete.
[0024] Preferably, the mass ratio of the sea-island fiber, graphene, nano-silicon dioxide and modified chitosan is 1g:30-40mg:0.3-0.5g:0.1-0.2g.
[0025] By adopting the above technical scheme, the mass ratio of the sea island fiber, graphene, nano-silica and modified chitosan is further limited within a certain range, thereby improving the comprehensive performance of the sea island fiber, nano-silica can be loaded on the surface of graphene, and graphene loaded with nano-silica can adhere to the surface of the sea island fiber. The modified chitosan makes the sea island fiber, graphene and nano-silica bond tightly, and the modified sea island fiber has a stable structure, thereby improving the strength and toughness of the sea island fiber. In the subsequent application in concrete, the sea island fiber, graphene, nano-silica and modified chitosan work synergistically to improve the strength, toughness, durability and stability of the concrete.
[0026] Preferably, the preparation method of the modified chitosan comprises the following steps: dispersing chitosan in acetic acid solution, adding silk fibroin powder and hydroxypropyl cellulose, stirring at a temperature of 60-65° C. for 1-2 hours, and drying to obtain modified chitosan.
[0027] By adopting the above technical solution, chitosan is dissolved in acetic acid solution to form a uniform system, silk fibroin powder has excellent mechanical properties, and hydroxypropyl cellulose has good film-forming properties and chemical stability. Silk fibroin powder can be dispersed in the structure of chitosan, chitosan and hydroxypropyl cellulose are bonded by hydrogen bonds, the chemical structure of chitosan is changed, a new chemical structure is formed, and the mechanical properties and film-forming properties of chitosan are improved.
[0028] Stirring at 60-65°C can promote the interaction between chitosan, silk powder and hydroxypropyl cellulose, making the reaction more complete and uniform. The obtained modified chitosan has excellent mechanical strength, toughness, viscosity and film-forming properties, and is subsequently used in modified sea-island fibers to improve the adhesion between the sea-island fibers and other components.
[0029] Preferably, the mass ratio of the chitosan, silk fibroin powder and hydroxypropyl cellulose is 1:0.3-0.4:0.1-0.2.
[0030] By adopting the above technical solution, the mass ratio of chitosan, silk powder and hydroxypropyl cellulose is further limited within a certain range, the comprehensive performance of modified chitosan is improved, chitosan and hydroxypropyl cellulose form a fiber network through hydrogen bonding, increase the viscosity and toughness of the system, and silk powder can be dispersed in the structure of chitosan to improve its mechanical properties. Chitosan, silk powder and hydroxypropyl cellulose have a synergistic effect, which jointly improves the viscosity, mechanical properties and stability of modified chitosan, and subsequently helps the sea island fiber to be mixed with other components to improve the corresponding performance of the sea island fiber.
[0031] In the second aspect, the present application also provides a method for preparing concrete containing heterogeneous mineral admixtures, comprising the following steps: stirring and mixing sand, gravel, silicate cement, fly ash, construction waste, deionized water, modified sea island fiber, montmorillonite, and water reducer to obtain concrete containing heterogeneous mineral admixtures.
[0032] By adopting the above technical scheme and the above preparation method, the operation is simple and the process time is short, which helps to improve the production efficiency of preparing concrete containing heterogeneous mineral admixtures. The obtained concrete containing heterogeneous mineral admixtures has good mechanical properties.
[0033] In summary, this application has the following beneficial effects: 1. In this application, construction waste is used as one of the raw materials of concrete to achieve resource recycling. Construction waste, sand, gravel and fly ash are mixed to improve the strength, durability and impermeability of concrete. Water reducer can significantly improve the workability of concrete, including fluidity, cohesion and water retention, making concrete easier to operate during pouring and molding, and reducing the risk of stratification and segregation.
[0034] 2. In this application, the modified island fiber is added to the concrete to improve the wear resistance, toughness and mechanical properties of the concrete, effectively inhibit the shrinkage cracks of the concrete during the hardening process, and improve the crack resistance of the concrete. The modified island fiber forms a three-dimensional network in the concrete, which can absorb and disperse stress and prevent the expansion of cracks.
[0035] 3. In the present application, montmorillonite can participate in the hydration process of cement, generate a large amount of CSH gel, fill the micropores and microcracks in the concrete, increase the bonding force of each component, significantly improve the microstructure of the concrete, improve its density, and subsequently improve the mechanical properties of the concrete. The concrete obtained by mixing various raw material components has good mechanical properties, crack resistance, durability and structural strength. DETAILED DESCRIPTION
[0036] The present application is further described in detail below in conjunction with embodiments.
[0037] The raw materials used in the examples and comparative examples can all be obtained commercially.
[0038] Example of preparation of construction waste Preparation Example 1-1 The method for preparing construction waste comprises the following steps: (1) 1.5 kg of construction waste was crushed into pieces with a particle size of 1-3 mm, then dispersed in 2 L of anhydrous ethanol, soaked for 1.5 h, dried, and then dispersed in 2.5 L of deionized water, silane coupling agent KH-550 was added, stirred for 1.5 h, filtered, and dried to obtain pretreated construction waste; (2) crushing the bamboo, passing through a 60-mesh sieve, and then dispersing it in 1.5 L of 8% sodium hydroxide solution, stirring for 1.5 h, washing with water, and drying to obtain pretreated bamboo powder; (3) The pretreated construction waste of step (1) was dispersed in 5.5 L of deionized water, and the pretreated bamboo powder and modified peach gum powder of step (2) were added, stirred at a temperature of 75° C. for 1.5 h, and dried to obtain construction waste.
[0039] Construction waste includes broken bricks and brick and tile fragments.
[0040] The mass ratio of construction waste, bamboo and modified peach gum powder is 1:0.5:0.09.
[0041] The preparation method of modified peach gum powder comprises the following steps: dispersing 1 kg of peach gum in 2 L of deionized water at a temperature of 70 DEG C, adding 0.2 kg of citric acid, sodium carboxymethyl cellulose and slag powder, stirring for 2.5 hours, drying and grinding to obtain modified peach gum powder.
[0042] The mass ratio of peach gum, sodium carboxymethyl cellulose and slag powder is 1:0.2:0.5.
[0043] Preparation Example 1-2 The difference from Preparation Example 1-1 is that in step (2), no bamboo is added.
[0044] Preparation Example 1-3 The difference from Preparation Example 1-1 is that in step (3), no modified peach gum powder is added.
[0045] Preparation Example 1-4 The difference from Preparation Example 1-1 is that the mass ratio of construction waste, bamboo and modified peach gum powder is 1:0.7:0.08.
[0046] Preparation Example 1-5 The difference from Preparation Example 1-1 is that the mass ratio of construction waste, bamboo and modified peach gum powder is 1:0.1:0.15.
[0047] Preparation Example 1-6 The difference from Preparation Example 1-1 is that in the preparation method of the modified peach gum powder, no sodium carboxymethyl cellulose is added.
[0048] Preparation Example 1-7 The difference from Preparation Example 1-1 is that no slag powder is added in the preparation method of the modified peach gum powder.
[0049] Preparation Example 1-8 The difference from Preparation Example 1-1 is that the mass ratio of peach gum, sodium carboxymethyl cellulose and slag powder is 1:0.3:0.4.
[0050] Preparation Example 1-9 The difference from Preparation Example 1-1 is that the mass ratio of peach gum, sodium carboxymethyl cellulose and slag powder is 1:0.6:0.1.
[0051] Preparation example of modified sea-island fiber Preparation Example 2-1 The preparation method of modified sea island fiber comprises the following steps: (1) 1.3 kg of sea-island fibers were dispersed in 1.8 L of ammonia water, stirred for 1.5 h, washed with water, and then dispersed in 2 L of anhydrous ethanol, soaked for 20 min, and dried to obtain pretreated sea-island fibers; ammonia water was purchased from Shandong Xinyi Biotechnology Co., Ltd.; (2) dispersing graphene in 1 L of ethylene glycol, adding nano-silica, ultrasonicating for 1.5 h, filtering, and drying to obtain pretreated graphene; (3) The pretreated sea island fibers of step (1) were dispersed in 3.5 L of deionized water, and the pretreated graphene and modified chitosan of step (2) were added. The mixture was stirred at 85° C. for 3 h, and dried to obtain modified sea island fibers.
[0052] The mass ratio of the sea-island fiber, graphene, nano-silica and modified chitosan is 1g:30mg:0.5g:0.2g.
[0053] The preparation method of modified chitosan comprises the following steps: dispersing 1 kg of chitosan in 2 L of acetic acid solution with a mass concentration of 12%, adding silk fibroin powder and hydroxypropyl cellulose, stirring at a temperature of 65° C. for 1.5 h, and drying to obtain modified chitosan; the silk fibroin powder is purchased from Hangzhou Linran Biotechnology Co., Ltd.
[0054] The mass ratio of chitosan, silk fibroin powder and hydroxypropyl cellulose is 1:0.3:0.2.
[0055] Preparation Example 2-2 The difference from Preparation Example 2-1 is that in step (2), no graphene is added.
[0056] Preparation Example 2-3 The difference from Preparation Example 2-1 is that in step (2), no nano-silicon dioxide is added.
[0057] Preparation Example 2-4 The difference from Preparation Example 2-1 is that in step (3), no modified chitosan is added.
[0058] Preparation Example 2-5 The difference from Preparation Example 2-1 is that the mass ratio of the sea-island fiber, graphene, nano-silica and modified chitosan is 1 g:40 mg:0.3 g:0.1 g.
[0059] Preparation Example 2-6 The difference from Preparation Example 2-1 is that the mass ratio of the sea-island fiber, graphene, nano-silica and modified chitosan is 1 g:25 mg:0.1 g:0.5 g.
[0060] Preparation Example 2-7 The difference from Preparation Example 2-1 is that no silk fibroin powder is added in the preparation method of modified chitosan.
[0061] Preparation Example 2-8 The difference from Preparation Example 2-1 is that hydroxypropyl cellulose is not added in the preparation method of modified chitosan.
[0062] Preparation Example 2-9 The difference from Preparation Example 2-1 is that the mass ratio of chitosan, silk fibroin powder and hydroxypropyl cellulose is 1:0.4:0.1.
[0063] Preparation Example 2-10 The difference from Preparation Example 2-1 is that the mass ratio of chitosan, silk fibroin powder and hydroxypropyl cellulose is 1:0.1:0.8. Example
[0064] Example 1 A concrete containing heterogeneous mineral admixtures, comprising the following raw materials by weight: 80 kg of sand, 120 kg of gravel, 50 kg of Portland cement, 30 kg of fly ash, 40 kg of construction waste, 80 kg of deionized water, 35 kg of modified sea island fiber, 25 kg of montmorillonite, and 3 kg of water reducing agent; The preparation method of the concrete containing heterogeneous mineral admixtures comprises the following steps: sand, gravel, silicate cement, fly ash, construction waste, deionized water, modified sea island fiber, montmorillonite and water reducing agent are stirred and mixed evenly to obtain concrete containing heterogeneous mineral admixtures.
[0065] The water reducing agent is sodium lignin sulfonate.
[0066] The construction waste was prepared by using Preparation Example 1-1; the modified sea island fiber was prepared by using Preparation Example 2-1.
[0067] Example 2 A concrete containing heterogeneous mineral admixtures, which differs from Example 1 in that, by weight, it includes the following raw materials: 90 kg of sand, 130 kg of gravel, 60 kg of silicate cement, 40 kg of fly ash, 50 kg of construction waste, 100 kg of deionized water, 45 kg of modified sea island fiber, 30 kg of montmorillonite, and 5 kg of water reducer.
[0068] Example 3 A concrete containing heterogeneous mineral admixtures, which differs from Example 1 in that construction waste is prepared using Preparation Example 1-2.
[0069] Example 4 A concrete containing heterogeneous mineral admixtures, which is different from Example 1 in that construction waste is prepared using Preparation Examples 1-3.
[0070] Example 5 A concrete containing heterogeneous mineral admixtures, which differs from Example 1 in that construction waste is prepared using Preparation Examples 1-4.
[0071] Example 6 A concrete containing heterogeneous mineral admixtures, which is different from Example 1 in that construction waste is prepared using Preparation Examples 1-5.
[0072] Example 7 A concrete containing heterogeneous mineral admixtures, which is different from Example 1 in that construction waste is prepared using Preparation Examples 1-6.
[0073] Example 8 A concrete containing heterogeneous mineral admixtures, which differs from Example 1 in that construction waste is prepared using Preparation Examples 1-7.
[0074] Example 9 A concrete containing heterogeneous mineral admixtures, which is different from Example 1 in that construction waste is prepared using Preparation Examples 1-8.
[0075] Example 10 A concrete containing heterogeneous mineral admixtures, which is different from Example 1 in that construction waste is prepared using Preparation Examples 1-9.
[0076] Embodiment 11 A concrete containing heterogeneous mineral admixtures, which differs from Example 1 in that the modified sea-island fiber is prepared using Preparation Example 2-2.
[0077] Example 12 A concrete containing heterogeneous mineral admixtures, which differs from Example 1 in that the modified sea-island fiber is prepared using Preparation Example 2-3.
[0078] Example 13 A concrete containing heterogeneous mineral admixtures, which differs from Example 1 in that the modified sea-island fibers are prepared using Preparation Examples 2-4.
[0079] Embodiment 14 A concrete containing heterogeneous mineral admixtures, which differs from Example 1 in that the modified sea-island fibers are prepared using Preparation Examples 2-5.
[0080] Embodiment 15 A concrete containing heterogeneous mineral admixtures, which is different from Example 1 in that the modified sea-island fibers are prepared using Preparation Examples 2-6.
[0081] Example 16 A concrete containing heterogeneous mineral admixtures, which differs from Example 1 in that the modified sea-island fibers are prepared using Preparation Examples 2-7.
[0082] Embodiment 17 A concrete containing heterogeneous mineral admixtures, which differs from Example 1 in that the modified sea-island fibers are prepared using Preparation Examples 2-8.
[0083] Embodiment 18 A concrete containing heterogeneous mineral admixtures, which differs from Example 1 in that the modified sea-island fibers are prepared using Preparation Examples 2-9.
[0084] Embodiment 19 A concrete containing heterogeneous mineral admixtures, which differs from Example 1 in that the modified sea-island fibers are prepared using Preparation Examples 2-10.
[0085] Comparative Example Comparative Example 1 A concrete containing heterogeneous mineral admixtures, which differs from Example 1 in that no construction waste is added.
[0086] Comparative Example 2 A concrete containing heterogeneous mineral admixtures, which is different from Example 1 in that the construction waste is purchased from Jiangsu Xiabosi Environmental Technology Co., Ltd.
[0087] Comparative Example 3 A concrete containing heterogeneous mineral admixtures, which differs from Example 1 in that modified sea-island fibers are not added.
[0088] Comparative Example 4 A concrete containing heterogeneous mineral admixtures, which differs from Example 1 in that the modified sea-island fibers are replaced by an equal amount of sea-island fibers.
[0089] Performance testing The concrete containing heterogeneous mineral admixtures prepared in Examples 1-19 and Comparative Examples 1-4 was subjected to performance tests. The compressive strength, splitting tensile strength, 28d shrinkage and 1h slump were tested in accordance with the Standard for Test Methods for Mechanical Properties of Ordinary Concrete (GB / T50081-2002). The surface of each group of samples was observed to see if there were any cracks, and the length of the cracks was recorded. The test samples were standard cubic specimens of 150mm×150mm×150mm. The test results are shown in Table 1.
[0090] Table 1 Test data of embodiments and comparative examples It can be seen from Table 1 that the concrete containing heterogeneous mineral admixtures prepared in Examples 1-2 of the present application has good mechanical properties and mechanical strength. Among them, the compressive strength of Example 1 at 7d reaches 56.2MPa, the compressive strength at 7 days reaches 73.9MPa, the splitting tensile strength at 28d is 7.98MPa, the slump 1h is 128mm, the shrinkage rate at 28d is 0.012mm / m, and there are no cracks, indicating that the prepared concrete containing heterogeneous mineral admixtures has good mechanical properties and mechanical strength, and the various components cooperate with each other, which helps to reduce microcracks in the concrete, improve the strength and durability of the concrete, and subsequently extend the service life of the building.
[0091] In the preparation method of construction waste of Examples 3-4, bamboo and modified peach gum powder are not added respectively, and the mass ratio of construction waste, bamboo and modified peach gum powder is changed in Examples 5-6. It can be seen from Table 1 that the test results of compressive strength, splitting tensile strength, slump, shrinkage and crack resistance of Examples 3-4 are significantly worse than those of Examples 1-2 and Example 5, while the test results of the corresponding properties of Example 6 are better than those of Examples 3-4, but worse than those of Examples 1 and Example 5, indicating that bamboo powder can be loaded on the surface and pores of construction waste, and modified peach gum powder has good viscosity, so that bamboo powder adheres to the surface of construction waste and fills the pores of bamboo powder and construction waste. The combination of construction waste, bamboo and modified peach gum powder has a synergistic effect, which jointly improves the mechanical properties and mechanical structure of construction waste, and subsequently increases the crack resistance and compression resistance of concrete.
[0092] In the preparation method of modified peach gum powder in Examples 7-8, sodium carboxymethyl cellulose and slag powder are not added respectively. In Examples 9-10, the mass ratio of peach gum, sodium carboxymethyl cellulose and slag powder is changed. It can be seen from Table 1 that the test results of compressive strength, splitting tensile strength, slump, shrinkage and crack resistance of Examples 7-8 are significantly better than those of Example 4. The test results of the corresponding properties of Example 10 are better than those of Examples 7-8, but worse than those of Examples 1 and 9, indicating that slag powder has good mechanical properties, crack resistance and durability, and can be embedded in the system structure formed by peach gum and sodium carboxymethyl cellulose to improve the mechanical properties of the system. Peach gum, sodium carboxymethyl cellulose and slag powder have a synergistic effect, which is subsequently applied to construction waste to improve the crack resistance, compressive strength and durability of construction waste, thereby improving the corresponding properties of concrete.
[0093] The preparation method of the modified sea-island fiber in Examples 11-13 does not add graphene, nano-silica and modified chitosan respectively, and Examples 14-15 change the mass ratio of the sea-island fiber, graphene, nano-silica and modified chitosan. It can be seen from Table 1 that the test results of the compressive strength, splitting tensile strength, slump, shrinkage and crack resistance of Examples 11-13 are significantly worse than those of Examples 1-2 and Example 14, while the test results of the corresponding properties of Example 15 are better than those of Examples 11-13, but worse than those of Examples 1 and 14, indicating that nano-silica can be loaded on the surface of graphene, and graphene can adhere to the surface of the sea-island fiber. The modified chitosan makes the sea-island fiber, graphene and nano-silica bond tightly, thereby improving the strength and toughness of the sea-island fiber. In the subsequent application in concrete, the sea-island fiber, graphene, nano-silica and modified chitosan work synergistically to improve the strength, toughness, durability and stability of the concrete.
[0094] The preparation methods of modified chitosan in Examples 16-17 do not add silk fibroin powder and hydroxypropyl cellulose respectively, and Examples 18-19 change the mass ratio of chitosan, silk fibroin powder and hydroxypropyl cellulose. It can be seen from Table 1 that the test results of compressive strength, splitting tensile strength, slump, shrinkage rate and crack resistance of Examples 16-17 are significantly better than those of Example 13, and the test results of corresponding properties of Example 19 are better than those of Examples 16-17, but worse than those of Example 1 and Example 18, indicating that a fiber network is formed between chitosan, silk fibroin powder and hydroxypropyl cellulose, which increases the viscosity and toughness of the system and improves its mechanical properties, which is helpful for mixing the island fiber with other components and improving the corresponding properties of the island fiber.
[0095] Comparative Examples 1 and 3 do not add construction waste and modified sea island fibers, respectively. As can be seen from Table 1, compared with Example 1, the test results of compressive strength, splitting tensile strength, slump, shrinkage and crack resistance of Comparative Examples 1 and 3 are significantly worse than those of Examples 1-2, indicating that the mixing of construction waste, sand, gravel and fly ash improves the strength, durability and impermeability of concrete. The modified sea island fibers effectively inhibit shrinkage cracks in concrete during the hardening process and improve the crack resistance of concrete. The modified sea island fibers form a three-dimensional network in concrete, which can absorb and disperse stress and prevent the expansion of cracks.
[0096] In Comparative Examples 2 and 4, commercially available construction waste and modified sea-island fibers were replaced with equal amounts of sea-island fibers, respectively. As can be seen from Table 1, the test results of compressive strength, splitting tensile strength, slump, shrinkage and crack resistance of Comparative Examples 2 and 4 are significantly worse than those of Examples 1-2, but better than those of Comparative Examples 1 and 3, indicating that the construction waste and modified sea-island fibers prepared in the present application have better mechanical properties, thereby improving the mechanical properties of concrete and maintaining the structural strength and stability of concrete.
[0097] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A concrete containing heterogeneous mineral admixtures, characterized in that: The following raw materials are included in parts by weight: 80-90 parts of sand, 120-130 parts of gravel, 50-60 parts of silicate cement, 30-40 parts of fly ash, 40-50 parts of construction waste, 80-100 parts of deionized water, 35-45 parts of modified sea island fiber, 25-30 parts of montmorillonite, and 3-5 parts of water reducing agent.
2. The concrete containing heterogeneous mineral admixtures according to claim 1, characterized in that: The method for preparing the construction waste comprises the following steps: (1) crushing the construction waste into pieces with a particle size of 1-3 mm, then dispersing them in anhydrous ethanol, soaking them for 1-2 hours, drying them, and then dispersing them in deionized water, adding a silane coupling agent, stirring them for 1-2 hours, filtering them, and drying them to obtain pretreated construction waste; (2) crushing the bamboo, sieving, and then dispersing in a sodium hydroxide solution, stirring for 1-2 hours, washing with water, and drying to obtain pretreated bamboo powder; (3) Dispersing the pretreated construction waste in step (1) in deionized water, adding the pretreated bamboo powder and modified peach gum powder in step (2), stirring at a temperature of 70-75° C. for 1-2 hours, and drying to obtain construction waste.
3. The concrete containing heterogeneous mineral admixtures according to claim 2, characterized in that: The mass ratio of the construction waste, bamboo and modified peach gum powder is 1:0.5-0.7:0.08-0.
09.
4. The concrete containing heterogeneous mineral admixtures according to claim 2, characterized in that: The preparation method of the modified peach gum powder comprises the following steps: dispersing peach gum in deionized water at a temperature of 70-75° C., adding citric acid, sodium carboxymethyl cellulose and slag powder, stirring for 2-3 hours, drying and grinding to obtain the modified peach gum powder.
5. The concrete containing heterogeneous mineral admixtures according to claim 4, characterized in that: The mass ratio of the peach gum, sodium carboxymethyl cellulose and slag powder is 1:0.2-0.3:0.4-0.
5.
6. The concrete containing heterogeneous mineral admixtures according to claim 1, characterized in that: The preparation method of the modified sea island fiber comprises the following steps: (1) Dispersing the sea island fibers in ammonia water, stirring for 1-2 hours, washing with water, and then dispersing in anhydrous ethanol, soaking, and drying to obtain pretreated sea island fibers; (2) dispersing graphene in ethylene glycol, adding nano-silicon dioxide, ultrasonicating for 1-2 hours, filtering and drying to obtain pretreated graphene; (3) Dispersing the pretreated sea-island fibers in step (1) in deionized water, adding the pretreated graphene and modified chitosan in step (2), stirring at a temperature of 80-85° C. for 2-3 h, and drying to obtain modified sea-island fibers.
7. The concrete containing heterogeneous mineral admixtures according to claim 6, characterized in that: The mass ratio of the sea island fiber, graphene, nano silicon dioxide and modified chitosan is 1g:30-40mg:0.3-0.5g:0.1-0.2g.
8. The concrete containing heterogeneous mineral admixtures according to claim 6, characterized in that: The preparation method of the modified chitosan comprises the following steps: dispersing chitosan in acetic acid solution, adding silk fibroin powder and hydroxypropyl cellulose, stirring at a temperature of 60-65° C. for 1-2 hours, and drying to obtain the modified chitosan.
9. The concrete containing heterogeneous mineral admixtures according to claim 8, characterized in that: The mass ratio of the chitosan, silk fibroin powder and hydroxypropyl cellulose is 1:0.3-0.4:0.1-0.
2.
10. The method for preparing concrete containing heterogeneous mineral admixtures according to claim 1, characterized in that: The method comprises the following steps: mixing sand, gravel, silicate cement, fly ash, construction waste, deionized water, modified sea island fiber, montmorillonite and water reducing agent uniformly to obtain concrete containing heterogeneous mineral admixtures.